The effect of iso‐butanol‐diesel blends on engine performance - Al-Hasan, Mohammad I.; Al-Momany, Muntaser (Transport, 2008)
The effect of iso‐butanol addition to diesel fuel on engine performance parameters has been experimentally investigated. The used engine was a single cylinder four stroke CI engine Type Lister 1–8. The tests were performed at engine speed that ranges from 375 to 625 with an increment of 42 rpm at different loads and with 10, 20, 30 and 40% v/v iso‐butanol‐diesel fuel blends. The overall engine performance parameters measured included air‐fuel ratio (AFR), exhaust gas temperature, brake power (Bp ), brake specific fuel consumption (bsfc) and brake thermal efficiency (η th ). The experimental results show that AFR, exhaust gas temperature, (Bp ) and (ηbth ) decreased and bsfc increased with iso‐butanol addition compared to net diesel fuel. Also, the obtained results indicate that the engine performance parameters when using up to 30% iso‐butanol in fuel blends are better than that of 40%.First published online: 27 Oct 2010